Adaptive sliding mode disturbance rejection control with prescribed performance for robotic manipulators. (August 2019) - Jing, Chenghu; Xu, Hongguang; Niu, Xinjian
Abstract: This study proposes an adaptive sliding mode disturbance rejection control with prescribed performance for robotic manipulators. A transformation with respect to tracking error using certain performance functions is used to ensure the transient and steady-state performances of the trajectory tracking control for robotic manipulators. Using the transformed error, a nonsingular terminal sliding mode surface is proposed. A continuous terminal sliding mode control (SMC) is presented to stabilize the system. To compensate for the uncertainty and external disturbance, a novel sliding mode disturbance observer is proposed. Considering the unknown boundary of the derivative of a lumped disturbance, an adaptive law based on the idea of equivalent control is designed. Combining the adaptive law, continuous nonsingular terminal SMC, and sliding mode disturbance observer, the adaptive sliding mode disturbance rejection control with prescribed performance is developed. Simulations are carried out to demonstrate the effectiveness of the proposed approach. Highlights: A nonsingular terminal sliding mode surface is presented. A novel sliding mode disturbance rejection control is proposed. An adaptive law based on the ideal of equivalent control is introduced. The practical finite time convergence and prescribed performance are achieved.